Nomenklatorische Berichtigung von Ostryo-Quercetum pubescentis (Horvat 1959) Trinajstić 1977 - Poldini, Livio (Hacquetia, 2015)
In accordance with the codex of phytocoenological nomenclature, we have corrected the name of following plant community: Ostryo-Quercetum pubescentis (Horvat 1959) Trinajstič 1977 with the new name Aristolochio luteae-Quercetum pubescentis (Horvat 1959) Poldini nom. nov. hoc. loco.